Interactions between financial efficiency and sports performance: Data for a sustainable entrepreneurial approach of European professional football clubs - Miragaia, D. A. M. (2020)
Submitted by MIRAGAIA (damm@ubi.pt) on 2020-01-30T11:43:19Z No. of bitstreams: 1 10-1108_JEPP-D-18-00060.pdf: 322193 bytes, checksum: 1535ca34ada00ba22f9284fd274f3034 (MD5)